How to do an Altemeier perineal rectosigmoidectomy for full‐thickness rectal prolapse. Issue 5 (18th January 2021) - Sakata, Shinichiro; McKenna, Nicholas P.; Allawi, Ahmed; D'Angelo, Anne‐Lise D.; Chua, Heidi K.; Dozois, Eric J.
Abstract : Here, we offer a step‐by‐step description of the technique for an Altemeier perineal rectosigmoidectomy, which is our institution's preferred perineal approach for patients with full‐thickness rectal prolapse. This article is supplemented by a series of high‐quality clinical images that are available in Figs S1–S11 . The principles of this technique are to excise the rectal prolapse and improve structural support of the pelvic floor.